BrlA and AbaA Govern Virulence-Required Dimorphic Switch, Conidiation, and Pathogenicity in a Fungal Insect Pathogen - An-Xue Zhang (American Society for Microbiology, 2019)
ABSTRACT Dimorphic plant and human mycopathogens require a switch from the usual yeast growth to filamentous growth for host tissue penetration, and the switch is controlled by multiple signaling systems other than the central developmental pathway. Unlike these fungi, dimorphic insect mycopathogens usually grow by hyphal extension, infect the host by hyphal penetration through the insect cuticle, and switch to unicellular blastospores from the penetrating hyphae only after entry into the host hemocoel, where blastospore propagation by yeast-like budding accelerates host mummification. Here, we report a dependence of the virulence-required dimorphic transition on the central pathway activators BrlA and AbaA in Beauveria bassiana. Deletion of brlA or abaA abolished both aerial conidiation and submerged blastospore formation in vitro despite no negative impact on hyphal growth in various media, including a broth mimic of insect hemolymph. The hyphae of either deletion mutant lost insect pathogenicity through normal cuticle penetration, contrasting with a high infectivity of wild-type hyphae. The mutant hyphae injected into the host hemocoel failed to form blastospores, resulting in slower lethal action. Uncovered by transcriptomic analysis, several genes involved in host adhesion and cuticle degradation were sharply repressed in both deletion mutants versus wild type. However, almost all signaling genes homologous to those acting in the dimorphic switch of other fungi were not differentially expressed at a significant level and hence unlikely to be involved in shutting down the dimorphic switch of each deletion mutant. Therefore, like aerial conidiation, the submerged dimorphic switch in vitro and in vivo is a process of asexual development governed by the two central pathway activators in B. bassiana. IMPORTANCE Dimorphic insect mycopathogens infect the host by hyphal penetration through the host cuticle and switch from the penetrating hyphae to unicellular blastospores after entry into the host hemocoel, where blastospore propagation by yeast-like budding accelerates host mummification to death. The fungal virulence-required dimorphic switch is confirmed as a process of asexual development directly regulated by BrlA and AbaA, two key activators of the central developmental pathway in an insect mycopathogen. This finding unveils a novel mechanism distinct from the control of the dimorphic switch by multiple signaling systems other than the central developmental pathway in dimorphic plant and human mycopathogens, which switch from the usual yeast growth to filamentous growth required for pathogenicity through host tissue penetration.